THE ROLE AND TYPES OF FINANCIAL INSTRUMENTS IN THE DEVELOPMENT OF SOCIAL ENTREPRENEURSHIP - Nodir Khodjayev (Innovate Conferences, 2025)
This paper examines the role of financial instruments in supporting social entrepreneurship. It explores tools like grants, subsidies, concessional loans, and impact investments, highlighting global best practices and Uzbekistan’s experience. The study emphasizes the need for diverse, results-oriented financing to foster sustainable and inclusive social ventures.
Keywords: Social entrepreneurship, financial instruments, grants and subsidies, impact investing, crowdfunding, social impact bonds, venture philanthropy.